Applicability of Flours from Pigmented and Glutinous Rice in Gluten-Free Bread Baking - Burešová, Iva; Červenka, Libor; Šebestíková, Romana; Augustová, Monika; Jarošová, Alžběta (My University, 2023)
The flours from pigmented and glutinous rice have a great potential to increase the nutritional quality of gluten-free breads. The characteristics of whole-meal fine flours, slurries, doughs, and breads prepared from black, red, and white glutinous rice were, therefore, compared with commercially used refined fine and semi-coarse white rice flours. The pasting properties of different flours were strongly influenced by the type of rice they were made from. Slurries with red and glutinous flours exhibited a shift to a lower pasting temperature T0, lower values of hPeak and hFinal, as well as higher values of the breakdown and setback region than the slurries with refined flours. The slurry with black flour exhibited high values of viscosity h0 and breakdown, together with low values of hFinal, setback region and total setback. Bread characteristics were strongly correlated with the pasting properties. The presence of bran particles did not negatively impact loaf volume, crumb hardness, springiness, and chewiness. Some defects were observed in glutinous and red rice bread. Fine flour exhibited better baking performance than semi-coarse flour. Glutinous flour has the potential to become an ingredient in gluten-free baking. The applicability of various black and red rice flours may be limited by the flavor and the taste.
Využití mouky z pigmentované a glutinózní rýže při výrobě bezlepkového chleba
Keywords: black rice; red rice; glutinous rice; dough; slurry; rheology; bread quality; texture; applicability; černá rýže; červená rýže; glutinózní rýže; těsto; kaše; reologie; kvalita chleba; textura; využití